Foraging Behavior of the Swarm-founding Wasp Polybia (Trichothorax) sericea (Hymenoptera, Vespidae): Daily Resource Collection Activity and Flight Capacity - Bichara Filho, Carlos C.; Santos, Gilberto M. de M.; dos Santos Filho, Alberto B.; Santana-Reis, Vanessa P.; da Cruz, Jucelho D.; Gobbi, Nivar [UNESP] (California State University, 2010)
A study on the flight capacity and daily activity of Polybia (Trichothorax) sericea (Olivier, 1791) was conducted. The main foraging activity for resource collection in Polybia sericea, the collection of liquid food (glucidics) had an Efficiency Index (EI) of 59.11, followed by prey (EI = 13.40) and wood pulp (EI = 2.92) collection. We observed a circadian rhythm for resource foraging activities, with mean angle at 11:07 hours (Rayleigh r = 0.71; P<0.05). The logistic regression model using the quasi-Newton method provided appropriate description for flight capacity in Polybia sericea (X(2) = 79.62; gl = 1; p < 0.001). According to the model, the flight capacity of Polybia sericea is low, occurs in short distances, and this species presents an effective flying distance of approximately 75m measured from their nest and radium of action (flying and return to the nest) of 37.5m that means a foraging area of approximately 4418m(2).
Keywords: Ethology; social wasps; foraging; daily activity; flight capacity